Reduced Enzymatic Browning in Potato Tubers by Specific Editing of a Polyphenol Oxidase Gene via Ribonucleoprotein Complexes Delivery of the CRISPR/Cas9 System - González, Matías Nicolás; Massa, Gabriela Alejandra; Andersson, Mariette; Turesson, Helle; Olsson, Niklas; Fält, Ann-Sofie; Storani, Leonardo; Décima Oneto, Cecilia Andrea; Hofvander, Per; Feingold, Sergio Enrique (Frontiers in Plant Science, 2020)
Polyphenol Oxidases (PPOs) catalyze the conversion of phenolic substrates to quinones, leading to the formation of dark-colored precipitates in fruits and vegetables. This process, known as enzymatic browning, is the cause of undesirable changes in organoleptic properties and the loss of nutritional quality in plant-derived products. In potato (Solanum tubersoum L.), PPOs are encoded by a multi-gene family with different expression patterns. Here, we have studied the application of the CRISPR/Cas9 system to induce mutations in the StPPO2 gene in the tetraploid cultivar Desiree. We hypothesized that the specific knock outediting of this target gene would result in a lower PPO activity in the tuber with the consequent reduction of the enzymatic browning. Ribonucleoprotein complexes (RNPs), formed by two sgRNAs and Cas9 nuclease, was were transfected to potato protoplasts. Up to 68% of regenerated plants contained mutations in at least one allele of the target gene, while 24% of edited lines carried mutations in all four alleles. No off-target mutations were identified in other analyzed StPPO genes. Mutations induced in the four alleles of StPPO2 gene, led to lines with a reduction of up to 69% in tuber PPO activity and a reduction of 73% in enzymatic browning, compared to the control. Our results demonstrate that the CRISPR/Cas9 system can be applied to develop transgene-free potato varieties with reduced enzymatic browning in tubers, by the specific editing of a single member of the StPPO gene family.